Evaluation of the PPAR-[gamma] agonist pioglitazone in mild asthma: A double-blind randomized controlled trial - Anderson, J. R; Mortimer, K; Pang, L; Smith, K. M; Bailey, H; Hodgson, D. B; Shaw, D. E; Knox, A. J; Harrison, T. W (PloS one, 2016)
Peroxisome proliferator-activated receptor gamma (PPAR-[gamma]) is a nuclear receptor that modulates inflammation in models of asthma. To determine whether pioglitazone improves measures of asthma control and airway inflammation, we performed a single-center randomized, double-blind, placebo-controlled, parallel-group trial. Sixty-eight participants with mild asthma were randomized to 12 weeks pioglitazone (30 mg for 4 weeks, then 45 mg for 8 weeks) or placebo. The primary outcome was the adjusted mean forced expiratory volume in one second (FEV.sub.1) at 12 weeks. The secondary outcomes were mean peak expiratory flow (PEF), scores on the Juniper Asthma Control Questionnaire (ACQ) and Asthma Quality of Life Questionnaire (AQLQ), fractional exhaled nitric oxide (FeNO), bronchial hyperresponsiveness (PD.sub.20 ), induced sputum counts, and sputum supernatant interferon gamma-inducible protein-10 (IP-10), vascular endothelial growth factor (VEGF), monocyte chemotactic protein-1 (MCP-1), and eosinophil cationic protein (ECP) levels. Study recruitment was closed early after considering the European Medicines Agency's reports of a potential increased risk of bladder cancer with pioglitazone treatment. Fifty-five cases were included in the full analysis (FA) and 52 in the per-protocol (PP) analysis. There was no difference in the adjusted FEV.sub.1 at 12 weeks (-0.014 L, 95% confidence interval [CI] -0.15 to 0.12, p = 0.84) or in any of the secondary outcomes in the FA. The PP analysis replicated the FA, with the exception of a lower evening PEF in the pioglitazone group (-21 L/min, 95% CI -39 to -4, p = 0.02). We found no evidence that treatment with 12 weeks of pioglitazone improved asthma control or airway inflammation in mild asthma.